The Influence of Using Academic Information System on Private University Image and Its Impact to Competitive Advantage - ., Realize; Brahmasari, Ida Aju; Panjaitan, Hotman (Archives of Business Research, 2017)
Competition among colleges in getting new students is getting fiercer. They are required to be able to have competitive advantages through improving facilities and image of the college to students and candidate students. The population in this research is students who are at least in the second year and come from private universities that have used academic information system. This study uses structural Equation Modeling (SEM) with AMOS version 22 are applied as tools in analyzing data. The results of research drawn based on hypothesis analysis and some tests show that academic information system has a significant influence on the image directly and indirectly to the competitive advantage of private universities in Kepulauan Riau province. This shows that by using Academic Information System, the students are very helpful in lecture activities because it provides a good assessment on the college which will finally give good appraisal of the competitive advantage of private universities in Kepulauan Riau province.